2007
DOI: 10.1136/bmj.39350.500428.47
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidants and primary prevention of age related macular degeneration: systematic review and meta-analysis

Abstract: Objective To evaluate the effectiveness of dietary antioxidants in the primary prevention of age related macular degeneration (AMD). Design Systematic review and meta-analysis. Data sources Search of seven databases without limits on year or language of publication, and retrieval of references in pertinent reviews and articles. Methods Two reviewers independently searched the databases and selected the studies, using standardised criteria. Randomised clinical trials and prospective cohort studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(145 citation statements)
references
References 53 publications
2
137
0
6
Order By: Relevance
“…A meta-analysis published by Chong et al of randomized controlled trials reported an odds ratio of 0.75, which was obtained by pooling the results from two studies: the Rotterdam eye study [46] and the Beaver Dam eye study [40,47]. The results from subsequent meta-analyses performed by Chong et al [40] and by Evans and Lawrenson [35] did not support a specific role for vitamin E in the prevention of AMD. To explain the discordant data of dietary vitamin E compared with the supplements, Evans and Lawrenson concluded that dietary vitamin E might be a marker for other nutrients with a role in the susceptibility of AMD [35].…”
Section: Vitamin Ementioning
confidence: 97%
See 3 more Smart Citations
“…A meta-analysis published by Chong et al of randomized controlled trials reported an odds ratio of 0.75, which was obtained by pooling the results from two studies: the Rotterdam eye study [46] and the Beaver Dam eye study [40,47]. The results from subsequent meta-analyses performed by Chong et al [40] and by Evans and Lawrenson [35] did not support a specific role for vitamin E in the prevention of AMD. To explain the discordant data of dietary vitamin E compared with the supplements, Evans and Lawrenson concluded that dietary vitamin E might be a marker for other nutrients with a role in the susceptibility of AMD [35].…”
Section: Vitamin Ementioning
confidence: 97%
“…Data from the National Health and Nutrition Examination Survey, reported by Goldberg et al, showed a negative association between the frequency of fruit and vegetables rich in vitamin A consumed and the prevalence of AMD [16]. However, several subsequent studies and a large metaanalysis failed to confirm this association [20,22,39,40], and unexpectedly, one report even suggested an increased risk in the development of late AMD in participants who took vitamin A [41]. With these conflicting results, more research is needed regarding the association between vitamin A and AMD.…”
Section: Vitamin Amentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, while "The retina, with its high oxygen content and constant exposure to light, is particularly susceptible to oxidative damage" (Chong et al 2007), the meta-analysis of 12 studies did not show that antioxidant supplements prevented early AMD (Chong et al 2007). …”
Section: Photoreceptor Nervous Cellsmentioning
confidence: 99%